Evaluation of Patient’s Knowledge, Attitude, and Practice of Cross-Infection Control in Dentistry during COVID-19 Pandemic - Ahmed, Muhammad Adeel; Jouhar, Rizwan; Adnan, Samira; Ahmed, Naseer; Ghazal, Tuba; Adanir, Necdet (European Journal of Dentistry, 2020)
Objectives The aim of this study was to evaluate the patient’s knowledge, attitude, and practice of cross-infection control in dentistry during coronavirus diseases 2019 (COVID-19).Materials and Methods This cross-sectional observational study was conducted at Altamash Institute of Dental Medicine, Karachi from June 2020 to August 2020. A total of 775 patients participated to fill questionnaire. After scrutiny, 25 questionnaire forms were excluded due to incomplete information. Questionnaire was divided in to four sections. First section obtained patients sociodemographic information, while knowledge of patients regarding cross-infection control during COVID-19 pandemic was evaluated in second section. Similarly, the purpose of third section was to assess attitude and fourth section was designed to evaluate practice. Likert’s 3-point scale was used for registration of participant’s response. The reliability of questionnaire was assessed through Crohnbach’s α (α = 0.74). Statistical analysis was performed after entering data in to SPSS version 25. Independent t-test was used to evaluate the difference in patients’ knowledge, attitude, and practice. A p-value ≤ 0.05 was considered as statistically significant.Results Majority of the participants agreed that COVID-19 is a highly contagious disease (631, 97%) and daily screening of staff, dental assistants, dentists, and patients is necessary (568, 75.7%) along with proper sterilization of instruments and disinfection of dental operatory (650, 86.66%). A large number of participant also agreed that proper disposal of waste is utmost important for cross-infection control (601, 80.24%) and patient's waiting area should also be marked with social distancing sign (620, 82.66%). However, when asked about the common route of COVID-19 transmission in dentistry, 341 (45.5%) participants disagreed that it is not through aerosol (water droplets) generated during dental procedures.Conclusions Dental health professionals should take additional measures to educate dental patients on mechanism of potential spread of COVID-19 through the aerosols and droplets generated during dental procedures. They should also encourage the dental patients to be vigilant and question the cross-infection control measures practiced by the dentist to whom they go for dental treatment, and to decrease their chances of acquiring an infection during their visit to the dental office.
Keywords: COVID-19; cross-infection control; knowledge, attitude, and practice